Ideological aspects of models of protecting human interests (Eurasian Journal of Media and Communications, 2025)
This article discusses the ideological aspects of models for protecting human interests, empiricism in the process of classifying objects of interest, the theoretical unfoundedness of the proposed division, In the classification of interests in some literature, man is represented as a consuming being. Therefore, such classifications, in our opinion, are presented as models of human interests.